Finite element simulation of pole vaulting - Drücker, S.; Schneider, K.; Ghothra, N.-K.; Bargmann, S. (Sports Engineering, 2018)
Pole vaulting is one of the most spectacular disciplines in athletics. The evolution of world record heights is strongly influenced by the development of advanced poles and subsequent materials. Employing advanced, load-adjusted composites has resulted in a steady increase of the world record height. This study provides a framework for finite element simulations of pole vaulting with focus on the initial and boundary conditions as well as finite element choices. The influence of the pole bending stiffness on the achievable height is systematically simulated. Higher effective bending stiffness leads to higher pole vaulting heights. However, if a certain stiffness is exceeded, the vaulter will not be able to bend the pole enough which leads to failed attempts.